2004
DOI: 10.2460/ajvr.2004.65.1276
|View full text |Cite
|
Sign up to set email alerts
|

Use of pressure platform gait analysis in cats with and without bilateral onychectomy

Abstract: Gait analysis was successfully performed in cats with a pressure platform walkway. The absence of differences in PVF and VI between the 2 groups of cats suggests that bilateral forelimb onychectomy did not result in altered vertical forces measured more than 6 months after surgery in cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 17 publications
3
54
1
1
Order By: Relevance
“…Thus, clear agreement exists that cats are forelimb dominant, meaning that the breaking forces exerted on the forelimbs are generally greater than those exerted on the hindlimbs. Only Guillot et al (2012) calculated the % BM at the trot and reported a hindlimb PFz (average of both hindlimb PFz values) of 50.8% BM during the trot, which is higher than that during the walk as reported by Lascelles et al (2007) and Verdugo et al (2013), but similar to that reported by Romans et al (2004).…”
Section: Grfs In Sound Catssupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, clear agreement exists that cats are forelimb dominant, meaning that the breaking forces exerted on the forelimbs are generally greater than those exerted on the hindlimbs. Only Guillot et al (2012) calculated the % BM at the trot and reported a hindlimb PFz (average of both hindlimb PFz values) of 50.8% BM during the trot, which is higher than that during the walk as reported by Lascelles et al (2007) and Verdugo et al (2013), but similar to that reported by Romans et al (2004).…”
Section: Grfs In Sound Catssupporting
confidence: 79%
“…Table 1 provides an overview of the aims of all studies included in this systematic review. Four studies involved basic kinetic research in sound cats during locomotion (Lascelles et al, 2007;LeQuang et al, 2010;Verdugo et al, 2013;Corbee et al, 2014), three addressed osteoarthritis (OA) (Guillot et al, 2012Moreau et al, 2013), and three evaluated cats that had undergone onychectomy (Romans et al, 2004(Romans et al, , 2005Robinson et al, 2007). Apart from the study by Moreau et al (2013), five studies dealing with diseased cats compared them to a sound control group.…”
Section: Methodsmentioning
confidence: 98%
“…In fact, kinematics, ground reaction force determination, or both have been used in a variety of species such as elephants [33][34][35] , cattle 36 , horses [37][38][39][40] , dogs 4,[41][42][43][44][45] , cats 21,[46][47][48][49] , various rodents 3,8,50,51 , birds 4,[52][53][54][55] , and fish 56,57 (this list is by no means exhaustive). In the authors' experience, however, the use of mice is problematic given that mice are not easy to operantly condition to travel along a runway.…”
Section: Discussionmentioning
confidence: 99%
“…Though kinematic and ground reaction force determination requires additional time and expertise, compared to some other forms of locomotor analysis (e.g. endpoint measures, ordinal rating scales), the data obtained is sensitive, objective and quantitative for a variety of orthopedic [14][15][16][17][18][19][20][21][22] and neurologic 1-3, 23-32 models of disease, in a variety of species.…”
Section: Discussionmentioning
confidence: 99%
“…Τα τελευταία χρόνια μελετάται η χρήση μεθόδων για την εκτίμηση του πόνου στη γάτα σε εργαστηριακό περιβάλλον. Μια από αυτές στηρίζεται στην εφαρμογή θερμικών ερεθισμάτων στο δέρμα του ζώου (Dixon et al 2002) και μια άλλη στη μέτρηση της δύναμης που ασκείται από το άκρο κατά τη βάδιση πάνω σε ειδικούς διαδρόμους (pressure-platform gait analysis) (Romans et al 2004). Η τελευταία μέθοδος αποκτά και κλινικό ενδιαφέρον σε ό,τι αφορά κυρίως στον πόνο που προέρχεται από τα άκρα, όπως συμ βαίνει μετά από επέμβαση ονυχεκτομής, αφοΰ οι τιμές των μετρήσεων είναι συνάρτηση του τρόπου χρησιμο ποίησης του άκρου.…”
Section: αναγνώριση του πόνουunclassified